2009
DOI: 10.1007/s11258-009-9619-y
|View full text |Cite
|
Sign up to set email alerts
|

Ground vegetation dynamics in mountain spruce (Picea abies (L.) Karsten) forests recovering after air pollution stress impact

Abstract: Our study focuses on the ground vegetation dynamics and its dependence on microsite conditions in declined climax mountain Norway spruce forests during the recovery period (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) following upon the considerable decrease of SO 2 pollution. We showed that ground vegetation development shifted from prevailing mosses and vegetation-free sites covered with spruce litter to dominance by Avenella flexuosa during the earlier period of massive decline of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
(41 reference statements)
3
7
0
1
Order By: Relevance
“…In our study, we observed a strong increase in the cover as well as a species turnover in the bryophyte layer in the unlimed plots. Vávrová et al (2009) present similar results for the Krkonoše Mountains. The authors interpret the strong changes in the bryophyte layer as being mainly due to a reduced competition from Deschampsia flexuosa and Calamagrostis villosa.…”
Section: Why Do the Herb And Bryophyte Layers React So Differently?supporting
confidence: 76%
See 1 more Smart Citation
“…In our study, we observed a strong increase in the cover as well as a species turnover in the bryophyte layer in the unlimed plots. Vávrová et al (2009) present similar results for the Krkonoše Mountains. The authors interpret the strong changes in the bryophyte layer as being mainly due to a reduced competition from Deschampsia flexuosa and Calamagrostis villosa.…”
Section: Why Do the Herb And Bryophyte Layers React So Differently?supporting
confidence: 76%
“…So far, however, few studies have analysed the extent to which a decrease in S deposition led to regeneration of the forest floor vegetation. Only Vávrová et al (2009) document the decline in the coverage of grasses as well as an increase in the coverage of the bryophyte layer between 1995 and 2006 in spruce stands in the Krkonoše Mountains (Giant Mountains), in response to decreasing S deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Die hohe Artenzahl sowie der hohe Anteil gefährdeter Arten, welche im Rahmen der Studie auf Totholz festgestellt wurden, verdeutlicht die Bedeutung von Totholz als Besiedlungssubstrat für Moose in Waldökosystemen. Nach Jahrzehnten extrem hoher Säureeinträge konnte in den letzten beiden Jahrzehnten eine Regeneration der Moosschicht in Waldökosystemen des Erzgebirges und des Riesengebirges dokumentiert werden ( Baumann et al 2022, Vávrová et al 2009). Für viele Arten ließ sich dabei eine initiale Besiedlung von Totholz beobachten, v. a. von Durchforstungsresten auf Rückegassen, von wo aus dann in einem zweiten Schritt die Wiederausbreitung auf dem Waldboden erfolgte ( Baumann 2009).…”
Section: Diskussionunclassified
“…Most of the catchments are climatically and lithologically predisposed to be sensitive to acidification, with the exception that PLB is well buffered by its ultrabasic bedrock [47]. The three catchments UDL, UHL, and JEZ were most exposed to direct air pollution in the second half of the 20th century and suffered from large-scale deforestation that reached its maximum in the mid of 1990s [44,48]. Locations of stream catchments within the GEOMON monitoring network in the Czech Republic.…”
Section: Study Sitesmentioning
confidence: 99%